2021
DOI: 10.3389/fendo.2021.581134
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights Into Monogenic Obesity Syndrome Due to INPP5E Gene Variant: A Case Report of a Female Patient

Abstract: A Caucasian girl with consanguineous parents presented with early severe obesity and retinal dystrophy. A novel, homozygous gene truncating variant (c.1897C>T) in the INPP5E gene confirmed the diagnosis of MORMS (OMIM #610156). A novel clinical finding in the presented syndrome is progressive cone-rod type retinal dystrophy diagnosed at the age of four months that progressed in the 1st decade of life. Severe obesity, insulin resistance with hyperinsulinism, and impaired glucose tolerance developed along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…In vitro experiments also confirmed that these muted INPP5E exhibit decreased phosphatase activity and cause impaired PI distribution in cilia [81,83,[85][86][87]. On the other hand, MORM syndrome is resulted from C-terminal deletions of INPP5E (Table 1), which leads to loss of the CAAX motif and exclusion of INPP5E from the ciliary membrane without affecting the catalytic activity [23,88]. Correspondingly, in addition to similar symptoms as JBTS including intellectual disability and retinal dystrophy, MORM syndrome shows phenotypes unseen in JBTS, including obesity and micropenis, as observed in other ciliopathies such as Bardet-Biedl syndrome and Cohen syndrome (Figure 4 and Table 2) [23,88,89].…”
Section: Inpp5ementioning
confidence: 85%
See 1 more Smart Citation
“…In vitro experiments also confirmed that these muted INPP5E exhibit decreased phosphatase activity and cause impaired PI distribution in cilia [81,83,[85][86][87]. On the other hand, MORM syndrome is resulted from C-terminal deletions of INPP5E (Table 1), which leads to loss of the CAAX motif and exclusion of INPP5E from the ciliary membrane without affecting the catalytic activity [23,88]. Correspondingly, in addition to similar symptoms as JBTS including intellectual disability and retinal dystrophy, MORM syndrome shows phenotypes unseen in JBTS, including obesity and micropenis, as observed in other ciliopathies such as Bardet-Biedl syndrome and Cohen syndrome (Figure 4 and Table 2) [23,88,89].…”
Section: Inpp5ementioning
confidence: 85%
“…On the other hand, MORM syndrome is resulted from C-terminal deletions of INPP5E (Table 1), which leads to loss of the CAAX motif and exclusion of INPP5E from the ciliary membrane without affecting the catalytic activity [23,88]. Correspondingly, in addition to similar symptoms as JBTS including intellectual disability and retinal dystrophy, MORM syndrome shows phenotypes unseen in JBTS, including obesity and micropenis, as observed in other ciliopathies such as Bardet-Biedl syndrome and Cohen syndrome (Figure 4 and Table 2) [23,88,89]. Compared with JBTS-associated INPP5E mutants which lead to a loss of INPP5E activity in the whole cell and whole body, MORM-associated INPP5E mutants only damage the INPP5E activity in cilia but may increase the INPP5E activity in other cellular locales due to mislocalization.…”
Section: Inpp5ementioning
confidence: 99%
“…Pathogenic variants in another inositol phosphatase, INPP5E , leads to MORM syndrome, a ciliopathy characterised by intellectual disability, central obesity, retinal dystrophy and micropenis 35. Similarly, obesity has been noted in a patient with Joubert syndrome caused by truncating mutation in INPP5E 36. Both INPP5E and OCRL belong to inositol phosphatase class of proteins, and it is possible there are functional similarities in their role in phosphoinostide-3-kinase and mammalian target of rapamycin (mTOR)-related pathways and in ciliary function relevant to energy homeostasis and metabolic health35 37 38 that remains to be explored.…”
Section: Discussionmentioning
confidence: 99%